Endotoxin Uptake by S1 Proximal Tubular Segment Causes Oxidative Stress in the Downstream S2 Segment - Kalakeche, Rabih (American Society of Nephrology, 2011)
Gram-negative sepsis carries high morbidity and mortality, especially when complicated by acute kidney injury (AKI). The mechanisms of AKI in sepsis remain poorly understood. Here we used intravital two-photon fluorescence microscopy to investigate the possibility of direct interactions between filtered endotoxin and tubular cells as a possible mechanism of AKI in sepsis. Using wild-type (WT), TLR4-knockout, and bone marrow chimeric mice, we found that endotoxin is readily filtered and internalized by S1 proximal tubules through local TLR4 receptors and through fluid-phase endocytosis. Only receptor-mediated interactions between endotoxin and S1 caused oxidative stress in neighboring S2 tubules. Despite significant endotoxin uptake, S1 segments showed no oxidative stress, possibly as a result of the upregulation of cytoprotective heme oxygenase-1 and sirtuin-1 (SIRT1). Conversely, S2 segments did not upregulate SIRT1 and exhibited severe structural and functional peroxisomal damage. Taken together, these data suggest that the S1 segment acts as a sensor of filtered endotoxin, which it takes up. Although this may limit the amount of endotoxin in the systemic circulation and the kidney, it results in severe secondary damage to the neighboring S2 segments.